Solution. We write the equation as
"\\frac {dy} {dx} =\\frac {1-tan(x+y} {tan(x+y)}"
"tan(x+y)dy=(1-tan(x+y))dx"
"(tan(x+y)-1)dx+tan(x+y)dy=0"
Consider the equation as
Therefore
"N(x,y)=tan(x+y)"
"\\frac {\\partial M} {\\partial y}= \\frac {1} {cos^2 (x+y)}"
"\\frac {\\partial N} {\\partial x}= \\frac {1} {cos^2 (x+y)}""\\frac {\\partial M} {\\partial y} = \\frac {\\partial N} {\\partial x}"
This equation is an equation in full differentials. Let U(x,y) is solution of the equation. Therefore
Integrating x we get
where C(y) is function of y. Hence
"\\frac {\\partial U} {\\partial y}= tan(x+y)+C'(y)= tan(x+y)"
"C'(y)=0"
"C(y)=C"
where C is constant. Therefore get
where C is constant.
Answer.
where C is constant.
Comments
Leave a comment